The use of a virtual platform for english language teaching in times of home confinement in seventh grade students at Escuela Fiscal Mixta Enrique Gil Gilbert, school year 2020-2021 - Mite Rodríguez, Evelyn Alexandra (2021)
For many years, education remains a relevant topic through its evolution, trends, and models, producing great changes within a socio-cultural, political and technological context. Its constant praxis in the educational system has allowed the definition of more appropriate methodological strategies for the students ‘learning development. In Ecuador, in 2016, the Ministry of Labor issued ministerial agreement No. Mdt-2016- 0190, which establishes the teleworking modality in the public and private sectors as a mechanism for the development of non-face-to-face work. This type of work was legally unknown until it gained strength and became part of a habit in our society due to the need to continue working from homes due to the coronavirus which consists on a group of viruses that cause illnesses ranging from the common cold to more serious illnesses such as pneumonia. However, many teachers are not trained to adapt to a technological system, much less to change their old methodology for the use of virtual platforms (MorenoCorrea, 2020)............